Networking a beginner's guide - Hallberg, Bruce A. 1964- (McGraw-Hill Education, 2014)
Current, essential IT networking skills made easy! Thoroughly revised to cover the latest technologies, this practical resource provides you with a solid foundation in networking fundamentals. Networking: A Beginner's Guide, Sixth Edition discusses wired and wireless network design, configuration, hardware, protocols, security, backup, recovery, and virtualization. You'll also get step-by-step instructions for installing, configuring, and managing Windows Server 2012, Exchange Server 2013, Oracle Linux, and Apache. This is the perfect book for anyone starting a networking career or in need of an easy-to-follow refresher. Understand network cabling, topologies, hardware, and the OSI seven-layer model; Connect LANs and WANs; Configure network protocols, such as TCP/IP, IPX/SPX, SMTP, DHCP, HTTP, WINS, and more; Explore directory services, such as Microsoft's Active Directory, X.400, and LDAP; Enable and support remote network access; Secure your network and handle backup and disaster recovery; Select, install, and manage reliable network servers, including Windows Server 2012, Exchange Server 2013, Oracle Linux, and Apache; Manage network workstation computers; Design a robust network from the ground up; Work with virtualization technologies, such as Hyper-V, VMWare, and Oracle VM VirtualBox